2017
DOI: 10.1007/s00216-017-0358-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of an optimal filter substrate for the identification of small microplastic particles in food by micro-Raman spectroscopy

Abstract: When analysing microplastics in food, due to toxicological reasons it is important to achieve clear identification of particles down to a size of at least 1 μm. One reliable, optical analytical technique allowing this is micro-Raman spectroscopy. After isolation of particles via filtration, analysis is typically performed directly on the filter surface. In order to obtain high qualitative Raman spectra, the material of the membrane filters should not show any interference in terms of background and Raman signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 18 publications
0
95
0
Order By: Relevance
“…Furthermore, the use of imaging techniques coupled to spectroscopic approaches allows automatization of MP identification [16][17][18]. In addition to spectroscopic methods, another type of chemical identification is thermal analysis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of imaging techniques coupled to spectroscopic approaches allows automatization of MP identification [16][17][18]. In addition to spectroscopic methods, another type of chemical identification is thermal analysis [12].…”
Section: Introductionmentioning
confidence: 99%
“…The general scheme for single particle analysis of MP is a workup step for the extraction and purification of MP [10] after which all remaining particles-microplastic as well as residual environmental colloids-are deposited on a smooth filter surface. The smoothness of the filter is of high importance, as any subsequent measurement, be it Fourier-transform infrared spectroscopy (FTIR) or confocal Raman microspectroscopy, will depend on a flat surface to enable optimal focus on the particles [11,12]. This is especially true if automated routines are used, where particles are first identified by acquiring images for a morphological assessment, including the determination of the particle centers for the subsequent measurement.…”
Section: Introductionmentioning
confidence: 99%
“…For larger particles (>300 mm), it is advised to adhere particles to a flat base material such as double-sided tape on transparency paper, 244 or an aluminum sheet to minimize background fluorescence. 245 Particles should be clearly characterized (e.g., circled and numbered) to aid particle identification using the Raman microscope. For smaller particles (<300 mm) that cannot be manually picked, particles should be analyzed directly from a filter to avoid contamination or particle loss.…”
Section: Raman Microspectroscopy For Mp Analysismentioning
confidence: 99%
“…The favored filter materials are metal covered PC membranes ($US$20-50), e.g., gold coated 40,49,242 or aluminum coated. 245 Käppler et al 159,185 suggested a specially fabricated silicon membrane ($US$10-30) as a possible filter material for FPA-FT-IR and RM analysis, which was limited in pore size to 10 mm. In previous studies, aluminum oxide (e.g., Anodisc) membranes ($US$5-20) or GF filters were recommended (for particles > 100 mm).…”
Section: Raman Microspectroscopy For Mp Analysismentioning
confidence: 99%